Vitamin D Treatment Modulates Organic Dust–Induced Cellular and Airway Inflammatory Consequences. Issue 1 (20th December 2012) - Golden, Gregory A.; Wyatt, Todd A.; Romberger, Debra J.; Reiff, Daniel; McCaskill, Michael; Bauer, Christopher; Gleason, Angela M.; Poole, Jill A.
ABSTRACT Exposure to organic dusts elicits airway inflammatory diseases. Vitamin D recently has been associated with various airway inflammatory diseases, but its role in agricultural organic dust exposures is unknown. This study investigated whether vitamin D reduces organic dust–induced inflammatory outcomes in cell culture and animal models. Organic dust extracts obtained from swine confinement facilities induced neutrophil chemokine production (human IL‐8, murine CXCL1/CXCL2). Neutrophil chemokine induction was reduced in human blood monocytes, human bronchial epithelial cells, and murine lung slices pretreated with 1, 25‐(OH)2D3. Intranasal inhalation of organic dust extract induced neutrophil influx, and CXCL1/CXCL2 release was also decreased in mice fed a relatively high vitamin D diet as compared to mice fed a low vitamin D diet. These findings were associated with reduced tracheal epithelial cell PKCα and PKCε activity and whole lung TLR2 and TLR4 gene expression. Collectively, vitamin D plays a role in modulating organic dust–induced airway inflammatory outcomes. © 2012 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:77‐86, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21467